THE ECONOMIC IMPACT OF BELOTUR DISBURSEMENTS WITH THE BELO HORIZONTE CARNIVAL IN 2018: AN APPLICATION OF THE INPUT-OUTPUT MATRIX (Publicatio UEPG: Ciências Sociais Aplicadas, 2020)
This study deals with the estimation of the economic impacts provided by the BeloHorizonte Municipal Tourism Company (Belotur) disbursements in 2018. It also aimsto understand how the event intervened in order to understand the contributionsunder the lens of expanding revenue, generating employment and income from thedisbursements made by Belotur. The method used was the Input-Output Matrix. Forthe matrix construction, it was necessary to analyze the published extracts related toBelotur expenses with the carnival and to carry out a classification of thedisbursements of Belotur according to the National Classification of EconomicActivities - CNAE. After these procedures, it was possible to estimate the impacts ofcarnival, which resulted from Belotur's disbursements, have shown very positiveresults in the economy, significantly increasing the values of Minas Gerais’production, value added, work earnings of the local population and also provided thecreation of jobs.